2022
DOI: 10.7554/elife.79552
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation modulates allosteric regulation of PRPS

Abstract: Phosphoribosyl pyrophosphate (PRPP) is a key intermediate in the biosynthesis of purine and pyrimidine nucleotides, histidine, tryptophan, and cofactors NAD and NADP. Abnormal regulation of PRPP synthase (PRPS) is associated with human disorders, including Arts syndrome, retinal dystrophy, and gouty arthritis. Recent studies have demonstrated that PRPS can form filamentous cytoophidia in eukaryotes. Here, we show that PRPS forms cytoophidia in prokaryotes both in vitro and in vivo. Moreover, we solve two disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Point mutations at the interface can destroy filament assembly, resulting in decreased enzyme activity. This result supports the views we previously observed in prokaryotic cells (Hu et al ., 2022).…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…Point mutations at the interface can destroy filament assembly, resulting in decreased enzyme activity. This result supports the views we previously observed in prokaryotic cells (Hu et al ., 2022).…”
Section: Introductionsupporting
confidence: 94%
“…Taking advantage of cryo-EM and laser-scanning confocal microscopy, we have recently found that PRPS in E. coli forms cytoophidia as well. E. coli PRPS forms two types of filament in vitro and in vivo (Hu et al ., 2022). The E. coli PRPS type A filament attenuates the allosteric inhibition by ADP, while the E. coli PRPS type B filament may influence the binding of ATP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 20 different metabolic enzymes form filaments in cells, suggesting that filament assembly is a general mechanism for regulating multiple metabolic pathways (Hvorecny and Kollman, 2023; Lynch et al, 2020; Narayanaswamy et al, 2009; Noree et al, 2010; Park and Horton, 2019; Park and Horton, 2020; Shen et al, 2016; Simonet et al, 2020). For many metabolic enzymes, filament formation is an important mechanism for fine-tuning catalytic activity (Barry et al, 2014; Hansen et al, 2021; Hu et al, 2022; Hunkeler et al, 2018; Hvorecny et al, 2023; Lu et al, 2023; Lynch and Kollman, 2020; Lynch et al, 2017; Polley et al, 2019; Stoddard et al, 2020; Zhong et al, 2022). Here, we demonstrate that filament assembly itself can be directly tuned by phosphorylation, adding an additional layer to an already complex mode of regulation for IMPDH that occurs at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…PRPS formed filamentous structures in a variety of eukaryotic cells such as yeast, Drosophila oocytes, rat neurons, human fibroblasts [ 25 ] and zebrafish retinal epithelial cells [ 26 ]. Recently, we also found that PRPS can form filamentous structures in prokaryotes such as Escherichia coli in vitro and in vivo [ 1 ]. We further understood the filament structure E. coli PRPS (ecPRPS) at near atomic resolution using cryo-electron microscopy (cryo-EM).…”
Section: Introductionmentioning
confidence: 99%